THE EFFECT OF INFOGRAPHIC ON ENGLISH LANGUAGE EDUCATION STUDENTS’ SPEAKING COMPETENCE - Cahyani, N. M. A. M.; Sintya Desi, K.; Myartawan, I. P. N. W. (Universitas Pendidikan Ganesha, 2020)
This research aimed at investigating the effect of infographic towards university students’ speaking competence. The research design was a quasi-experiment with a post-test-only control group design. The research population included the 2nd semester students of English Language Education of UNDIKSHA Indonesia in academic year 2019/2020. Through lottery, the samples were divided into experimental group which was taught by using infographic and control group which was taught by using conventional strategy. The data were collected through post-test in a form of speaking performance. The data were analyzed using descriptive and inferential statistics analysis. The result of data analysis showed that the students in experimental group performed better than the students in control group. It was also supported by the descriptive statistics result which showed the mean score of experimental group (X̄= 82.89) was higher than the control group (X̄= 75.03). The result of the T-test showed that the value of the tobs was 5.422 meanwhile the value of tcv was 1.674 which means tobs was higher than tcv. Moreover, the significant value of the data was 0.001or less than 0.05. The result of effect size was 1.45 that belongs to the large effect category. Based on the findings, it was concluded that there was a significant effect of using infographic as a media on students’ speaking competence.Keywords: Infographic, Speaking competence, Instructional media